Does an elite education benefit health? Findings from the 1970 British Cohort Study. (10th May 2016) - Bann, David; Hamer, Mark; Parsons, Sam; Ploubidis, George B; Sullivan, Alice
Abstract: Background: Attending private school or a higher-status university is thought to benefit future earnings and occupational opportunities. We examined whether these measures were beneficially related to health and selected health-related behaviours in midlife. Methods: Data were from up to 9799 participants from the 1970 British birth Cohort Study. The high school attended (private, grammar or state) was ascertained at 16 years, and the university attended reported at 42 years [categorised as either higher (Russell Group) or normal-status institutions]. Self-reported health, limiting illness and body mass index (BMI) were reported at 42 years, along with television viewing, take-away meal consumption, physical inactivity, smoking and high risk alcohol drinking. Associations were examined using multiple regression models, adjusted for gender and childhood socioeconomic, health and cognitive measures. Results: Private school and higher status university attendance were associated with favourable self-rated health and lower BMI, and beneficially associated with health-related-behaviours. For example, private school attendance was associated with 0.56 [95% confidence interval (CI): 0.48, 0.65] odds of lower self-rated health [odds ratio (OR) for higher-status university: 0.32 (0.27, 0.37)]. Associations were largely attenuated by adjustment for potential confounders, except for those of private schooling and higher-status university attendance with lower BMI and television viewing, and less frequent take-away meal consumption. Conclusions: Private school and higher-status university attendance were related to better self-rated health, lower BMI and multiple favourable health behaviours in midlife. Findings suggest that type or status of education may be an important under-researched construct to consider when documenting and understanding socioeconomic inequalities in health.